2015
DOI: 10.1016/j.nima.2014.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy (<10keV) electron ionization and recombination model for a liquid argon detector

Abstract: Detailed understanding of the ionization process in noble liquid detectors is important for their use in applications such as the search for dark matter and coherent elastic neutrino-nucleus scattering. The response of noble liquid detectors to low-energy ionization events is poorly understood at this time. We describe a new simulation tool which predicts the ionization yield from electronic energy deposits (E < 10 keV) in liquid Ar, including the dependence of the yield on the applied electric drift field. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In addition, as the electron extraction field was changed in the experiment, the extent of recombination suppression in this above-EG region also changed, resulting a fielddependent background in the EEE study. For the lower energy L-shell 37 Ar decays, this effect was not observed, possibly because the recombination probability was negligible at all fields due to the extremely low ionization densities, as predicted by first-principal simulations in liquid argon [44]. Energey spectra of 37 Ar events measured at 6.0 kV/cm extraction field in the LF run.…”
Section: B 37 Ar Analysismentioning
confidence: 84%
“…In addition, as the electron extraction field was changed in the experiment, the extent of recombination suppression in this above-EG region also changed, resulting a fielddependent background in the EEE study. For the lower energy L-shell 37 Ar decays, this effect was not observed, possibly because the recombination probability was negligible at all fields due to the extremely low ionization densities, as predicted by first-principal simulations in liquid argon [44]. Energey spectra of 37 Ar events measured at 6.0 kV/cm extraction field in the LF run.…”
Section: B 37 Ar Analysismentioning
confidence: 84%
“…Typically these chambers operate with electric field strengths of less than 500 kV cm -1 . Foxe et al [80] have measured the energy distribution of the electrons ionized by high energy particles in liquid argon, and have shown that the majority of the ionized electrons have energies below 1 eV.…”
Section: Spatio-temporal Relaxation Of Electrons In Liquid Argonmentioning
confidence: 99%
“…The Noble Element Simulation Technique (NEST) incorporates a semi-empirical physical model of the generation of scintillation photons and ionization electrons from recoiling particles in liquid xenon [5][6][7]. In both argon [8] and helium [9], it is possible to calculate excitation and ionization in recoil cascades from first principles using measurements of the relevant interaction cross-sections. In xenon these cross sections have never been measured or calculated, rendering such predictions impossible.…”
Section: Introductionmentioning
confidence: 99%